Alignment Checkpoints Model for Evaluating Strategic Information Systems Planning in a Financial Organization in Malaysia - Adnan, Azman (2011)
Since the past few decades, business organizations have leveraged on the improving technology to achieve their corporate goal for higher profitability by maximizing the utilization of Information Technology (IT). Eventually, numerous models and frameworks of strategic alignment (SA) between the IT and Business strategies have been proposed by many researchers that had resulted in various opinions and arguments about the complexity of the situation due to certain factors involved and such predicament is known as the IT Productivity Paradox. Based on these arguments, this research has created a new model that functions as an instrument to evaluate the SA between the strategies. The concentration of this study is within the IT and Business strategies, evaluating the attributes involved at each process level to reach the state of SA. These attributes are derived from six selected renowned SA models i.e. the MIT90s (Morton, 1991), Strategic Alignment Model - SAM (Henderson & Venkatraman, 1993), The Alignment Model (Maes et. al., 2000), Co-variation Model of Strategic Alignment (Bergeron et. al., 2002), Organizational Systems Integration (OSI) model (Pollalis, 2003) and Dimensions of Strategic Alignment Model (Tallon & Kraemer, 2003) which were compared and evaluated to form the proposed model of this research known as the Alignment Checkpoints Model or ACM. What differs the ACM from other models is that the main strategy of a particular domain is further divided into sub-strategies known as the Component Strategy (CS). Subsequently, each and every process level involved in the CS will be evaluated at ground-level to detect compliance and discrepancies to achieve the objective of the main strategy. Unlike the research that requires statistical information about the users‟ satisfaction on a particular application software that is being implemented that may lead to factors of biasness, the expectation of this research is an actual success in IT implementations and support towards the Business strategy. Fundamentally, through a test conducted at a selected financial institution, the ACM aims and has succeeded at checking the process levels of IT support and implementations in the Systems Development Life Cycle (SDLC) process guided by the Strategic Information Systems Planning (SISP) that materializes the Business plans and objectives. Other value-added features of the ACM are its ability to also identify the compliance and discrepancies between other domains as well. With such holistic evaluation over all processes involved at every CS of a main strategy in an organization will result in equilibrium among these processes involved. Therefore, this allows for continuing research to those with interest in evaluating the alignment of other areas of concern. In this study, it has been found that well-aligned strategies of the IT and Business domains complemented by the SISP had resulted in a tremendous improvement and progress at organizational level. Therefore, the ACM is proven to be a very useful tool that may be used by other business organizations to ensure that every sector or domain in the organization is supporting each other to achieve a common goal.